Long Term Variceal Sclerotherapy: Is Endoscopic Sclerosis a Unique Therapeutic Approach and a True Alternative to Surgery?. Issue 1 (1991) - Paquet, K-J.; Lazar, A.; Rambach, W.
Abstract : Endoscopic sclerotherapy has been used to control acute variceal haemorrhage which persists despite conservative therapy, prevent recurrent variceal haemorrhage in patients with a history of oesophageal haemorrhage, and to prevent a haemorrhage in patients with oesophageal varices who never bled. In this short paper I will cover our personal experience with more than 2000 patients receiving particularly paravariceal endoscopic sclerotherapy of bleeding esophageal varices, and especially present the results of our prospective and controlled randomized trials (Table 1) and underline the thesis that endoscopic sclerotherapy and surgical procedures for patients with portal hypertension are complementary supporting measures or options.